Analysis of Methods to Correct Indonesian Language Spelling Errors in Thesis Writing Among Students of State University of Medan - Lubis, Fitriani; Safitri, Nurdina; Gultom, Paskah Monika Putri; Dwijaya, Nadiah; Dalimunthe, Mhd Sarwadin Ansori; Hia, Tasya Bernatha; Azhar, Fadly; Hutapea, Febrian P; Sianipar, Rosdintan Maria Melani (EDUCTUM: Journal Research, 2023)
This text discusses the editing of Indonesian language manuscripts using various linguistic techniques, encompassing on-screen and manual editing. Academic and developer-created editing applications for Android-based apps and web pages facilitate on-screen editing. Notable programs include jasa.id, lektur.id, typoonline.com, typograp.com, and SIPEBI (Indonesian Spelling Editing). These applications provide features to enhance the editing process for Indonesian language users, each having distinct strengths and weaknesses. They detect elements like standardized and non-standardized words, spelling variations, including capitalization, prepositions, numbers, and typing errors. Generalizing these aspects across sections is challenging, necessitating varied handling and corrections for each text or document. While these programs streamline editing, manual editing remains crucial due to unknown factors. Despite its time-consuming nature, manual editing excels in accuracy and coverage. In summary, these applications play a valuable role, but manual editing is indispensable for comprehensive and precise language refinement.